Methadone related deaths compared to all prescription related deaths. (December 2015) - Lev, Roneet; Petro, Sean; Lee, Ariella; Lee, Oren; Lucas, Jonathan; Castillo, Edward M.; Egnatios, Jeremy; Vilke, Gary M.
Highlights: The majority of methadone deaths came outside the PDMP system. A risk-benefit analysis should be made to consider changing existing laws. OTP should make it standard of care to check PDMP data on their patients. Abstract: Background: Methadone is increasingly implicated in unintentional overdose deaths. Despite major interventions, rates continue to remain high. One primary intervention, Prescription Drug Monitoring Programs (PDMP) are limited in their ability to impact this epidemic due to federal law restricting Opioid Treatment Programs (OTPs) from sharing data to PDMPs, despite being a major source of Methadone dispensing. Methods: This retrospective, observational study analyzed all prescription-related deaths occurring in San Diego County during the year 2013 with a specific focus on methadone-related deaths. All patients designated by medical examiner to have died by unintentional prescription were then referenced in the California PDMP, the Controlled Substance Utilization Review and Evaluation System (CURES). Results: As a whole, patients who died had a high number of average prescriptions, 21, and averaged 4.5 different providers, and three different pharmacies. Methadone-related deaths (MRD) accounted for 46 out of the 254 total patient deaths (18.1%). Methadone prescriptions were found in 14 patients with PDMP reports, 10 of who had methadone on toxicology report. Notably, 100% of methadone prescribed by primary care specialists. MRD patients were less likely to have toxicology reports matching PDMP data compared to other related drug deaths (20.6 vs. 61.2%, p < 0.0001). Of the 46 methadone deaths, only 10 (29.4%) had prescriptions for methadone recorded in the database. Out of the 51 patients with only one drug recorded at death, methadone was most common ( n = 12; 23.5%). While all deaths had a notably high rate of chronic prescriptions at death (68.8% compared to 2% for all patients in CURES), there was no significant difference between MRD and other drug-related deaths (73.5 vs. 67.8%, p = 0.68, respectively). MRD patients were less likely than other drug patients to have matching PDMP data without any illicit substance or alcohol (14.7 vs. 41.4%, p = 0.003, respectively). Conclusion: Methadone is a long-acting opioid that carries a higher risk profile than other opioids. In San Diego, the great majority of MRD had no data on methadone in the statewide PDMP database, bringing to question the restriction of OTP clinics from uploading information into the database. A risk-benefit analysis should be made to consider changing laws that would allow for OTP to input data into PDMP. OTP should make it standard of care to check PDMP data on their patients. Methadone prescribed for pain management should be limited to the most compliant patients.